Apigenin-7-O-glucoside alleviates DSS-induced colitis by improving intestinal barrier function and modulating gut microbiota. (May 2023) - Hu, Yeye; Guan, Xueting; He, Ziliang; Xie, Yuan; Niu, Zhiqiang; Zhang, Wei; Wang, Aoran; Zhang, Ji; Si, Chuanling; Li, Fu; Hu, Weicheng
Graphical abstract: Highlights: AG ameliorates DSS-induced colitis in mice. AG can inhibit MAPK pathway in DSS-induced colitis mice. AG can improve gut barrier integrity in DSS-induced colitis mice. AG significantly increase the abundance of Akkermansia. Abstract: Apigenin-7-O-glucoside (AG), a flavonoid glycoside, has been shown in vitro anti-inflammatory activities. To date, the mechanism of AG against colitis has not been reported. In this study, we investigated the role of AG in relieving colitis and explored its potential mechanisms in dextran sulfate sodium (DSS)-induced colitis mice. The results indicated oral administration of AG increased colon length and improved colonic histopathology. Besides, it dramatically restored the colonic expression of pro-inflammatory and anti-inflammatory mediators, as well as enhanced the expression of intestinal barrier markers such as ZO-1, occludin, claudin-1, and claudin-3. The mitogen-activated protein kinases (MAPKs) including ERK, JNK, and p38 were significantly inhibited. Moreover, 16S rDNA sequencing revealed that AG improved the abundance of Akkermansia, and reduced that of Bacteroides and Desulfovibrio . Taken together, AG supplementation relieved DSS-induced colitis by protecting the intestinal barrier, inhibiting the MAPK pathway, and modulating gut microbiota, which indicated that AG may be a good candidate therapeutic compound for sustaining gut health to lower the risk of colitis.